ANALISIS KEKUATAN RANGKA BODI BUS LISTRIK MD12E PERSEROAN TERBATAS MOBIL ANAK BANGSA DENGAN METODE ELEMEN HINGGA - Gustomo, Gigih; Anis, Samsudin (Journal of Mechanical Engineering Learning, 2020)
Abstract This study was aimed to determine the level of safety numbers and investigate the effect of the static load applied to the bus body frame structure on the von mises stress, displacement and deformed values ​​on the MD12E electric bus of PT. Mobil Anak Bangsa. This research was conducted with the computational method namely finite element method in the Autodesk Inventor Professional 2019 software. The analysis was carried out in the form of stress analysis. The object being analyzed is the MD12E electric bus body frame structure of PT. Mobil Anak Bangsa. The results of the analysis obtained on the MD12E electric bus body frame structure PT. Mobil Anak Bangsa shows the maximum value of von mises stress is 16.67 MPa, the minimum value is 5.628 x 10-05 MPa. For displacement obtained a maximum value of 0.4444 mm and a minimum value of 0.0 mm. The analysis also shows that the safety factor is 12.9. Based on the research results obtained from the analysis of the body structure framework of the prototype 3 electric bus of PT. Mobil Anak Bangsa is categorized as very safe because it has a high enough safety factor (12.9).